Peroxisome Proliferator-Activated Receptors and the Heart: Lessons from the Past and Future Directions - Wang-Soo Lee; Jaetaek Kim (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) belong to the nuclear family of ligand activated transcriptional factors and comprise three different isoforms, PPAR-α, PPAR-β/δ, and PPAR-γ. The main role of PPARs is to regulate the expression of genes involved in lipid and glucose metabolism. Several studies have demonstrated that PPAR agonists improve dyslipidemia and glucose control in animals, supporting their potential as a promising therapeutic option to treat diabetes and dyslipidemia. However, substantial differences exist in the therapeutic or adverse effects of specific drug candidates, and clinical studies have yielded inconsistent data on their cardioprotective effects. This review summarizes the current knowledge regarding the molecular function of PPARs and the mechanisms of the PPAR regulation by posttranslational modification in the heart. We also describe the results and lessons learned from important clinical trials on PPAR agonists and discuss the potential future directions for this class of drugs.